Free Radical Scavenging and Alpha/Beta-glucosidases Inhibitory Activities of Rambutan (Nephelium lappaceum L.) Peel Extract - Wahyu Widowati; Maesaroh Maesaroh; Nurul Fauziah; Pande Putu Erawijantari; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Diabetes mellitus (DM) is associated with oxidative reaction and hyperglycemic condition. Human body has an antioxidant defense system toward free radical, but overproduction of free radical causing imbalance condition between the free radical and the antioxidant defense in the body that lead to several diseases, including DM. Glucosidase is an enzyme that hydrolize carbohydrates causing increase of blood glucose level, so by inhibiting this enzyme blood glucose level in plasma could be effectively decreased. Rambutan (Nephelium lappaceum L.) peel has been reported to have many potential roles, such as antioxidant and anti-glycemia. Therefore our current study was conducted to evaluate possible effectivity of Rambutan peel to scavenge free radical and to inhibit α- and β-glucosidases. METHODS:Rambutan peel extraction (RPE) was performed based on maceration method. Geraniin was used as control. For antioxidant study, 2,2-diphenyl-1- picrylhydrazyl (DPPH) free radical scavenging test was performed. For glucosidase inhibitory activity study, α- and β-glucosidases inhibitory activity tests were performed. Results were analyzed for median of Inhibitory Concentration (IC50).RESULTS: The scavenging activity of RPE was comparable with Geraniin. Meanwhile, the α-glucosidase inhibitory activity of RPE was higher than the one of Geraniin. The α-glucosidase-inhibitory-activity IC50 of RPE and Geraniin were 0.106±0.080 μg/ml and 16.12±0.29 μg/ml, respectively. The β-glucosidase inhibitory activity of RPE was also higher than the one of Geraniin. The β-glucosidase-inhibitory-activity IC50 of RPE and Geraniin were 7.02±0.99 μg/ml and 19.81±0.66 μg/ml, respectively.CONCLUSION: Since RPE showed comparable free radical scavenging activity with Geraniin and higher α- and β-glucosidases inhibitory activities than Geraniin, RPE could be suggested as a promising antioxidant and antiglycemic agent. KEYWORDS: Nephelium lappaceum L., rambutan, hypoglycemic, antioxidant, free radical, diabetes mellitus, glucosidase, DPPH